The diagnosis and management of diabetes in Australia: Does the "Rule of Halves" apply?. (December 2020) - Sainsbury, Emma; Shi, Yumeng; Flack, Jeff; Colagiuri, Stephen
Abstract: The Rule of Halves (ROH) is a theoretical framework which states that roughly half of all people with a condition are diagnosed; half of those diagnosed receive care; half of those who receive care achieve their treatment targets; and half of those who reach their targets achieve the desired treatment outcomes. This review examined the applicability of the ROH to diabetes in Australia. Five databases were searched for articles and government reports published between January 2000 and August 2019. Data was extracted for each level of the framework, and pooled sample proportions calculated for the total population and sub-group analysis by ethnicity and type of diabetes. The results showed that 72% of people with diabetes are diagnosed. Approximately 50% are receiving standard care, and 40–60% are meeting treatment targets for HbA1c, blood pressure and lipid levels. Overall, Australia is doing better than the ROH when it comes to achieving treatment outcomes; prevalence of microvascular complications was 20–30% and cardiovascular disease 62%. Indigenous people were less likely to meet treatment targets and more likely to experience adverse complications of diabetes. This review indicates the ROH does generally apply for diabetes care and management in Australia, highlighting the need for further improvement.